2020
DOI: 10.1093/pch/pxaa003
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Acceptance and Commitment Therapy for parents of preterm infants

Abstract: The start of a parenting journey in the neonatal intensive care unit (NICU) presents many stressors to parents. Previous research has shown parents of infants admitted to the NICU experience heightened stress, anxiety, and depression. Mental health support varies across Canadian NICUs with mixed results. One promising intervention that has not been explored in the NICU is Acceptance and Commitment Therapy (ACT), a behavioural therapy that has had positive mental health-related outcomes in similar parental popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…community providers in the hospital) ( Brown & Menec, 2018 ). Promising NICU initiatives that incorporate some of these features include, (1) the Calgary Neonatal Transitional Care Program, that uses Clinical Nurse Specialists to deliver neonatal follow-up, in the home setting, post-NICU discharge ( Lasby et al, 2004 ); (2) the Transition Home Plus program, that incorporated supportive services both before and after discharge from the NICU including social worker support post discharge, a home visit by a Neonatal Nurse Practitioner, and integration with primary care providers post-discharge ( Liu et al, 2018 ) and (3) the Coached, Coordinated, Enhanced Neonatal Transition, a pilot intervention using a nurse navigator role, including care coordination up to 12 months post-NICU discharge ( Esser et al, 2019 ). Missing from these models, however, is the partnership with PHNs that that have the specific knowledge and skill related to navigating supportive services in the communities that the families live, as well as the expertise establishing relationships with adolescent parents and mobilizing their support networks.…”
Section: Discussionmentioning
confidence: 99%
“…community providers in the hospital) ( Brown & Menec, 2018 ). Promising NICU initiatives that incorporate some of these features include, (1) the Calgary Neonatal Transitional Care Program, that uses Clinical Nurse Specialists to deliver neonatal follow-up, in the home setting, post-NICU discharge ( Lasby et al, 2004 ); (2) the Transition Home Plus program, that incorporated supportive services both before and after discharge from the NICU including social worker support post discharge, a home visit by a Neonatal Nurse Practitioner, and integration with primary care providers post-discharge ( Liu et al, 2018 ) and (3) the Coached, Coordinated, Enhanced Neonatal Transition, a pilot intervention using a nurse navigator role, including care coordination up to 12 months post-NICU discharge ( Esser et al, 2019 ). Missing from these models, however, is the partnership with PHNs that that have the specific knowledge and skill related to navigating supportive services in the communities that the families live, as well as the expertise establishing relationships with adolescent parents and mobilizing their support networks.…”
Section: Discussionmentioning
confidence: 99%
“…21 22 However, there is a lack of direct support for parent psychosocial (psychological and social) needs, 23 and limited research on this area. 24 A systematic review of interventions for NICU parents including psychosocial support, education, and/or developmental interventions reported positive effect on depression and anxiety, but limited effect on stress. 14 Stress is a contributing factor to many mental disorders, and long-term stress increases the risk of depression and anxiety.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Research has shown that increasing psychological flexibility through mindfulness therapies reduced maternal depression during the NICU admission and after discharge. 58 ACT interventions can be delivered by a variety of trained facilitators, 24 and demonstrate improved mental health outcomes for parents of children with life-threatening illness, 59 asthma 60 and autism. 61 ACT may be more appropriate for parents in the NICU compared with interventions such as cognitive-behavioural therapy, 24 which demonstrates effectiveness in reducing depression but not anxiety for NICU mothers.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation